Infantile Abdominal and Pelvic Lipoblastomas: A Case Series - Guanà, Riccardo; Garofalo, Salvatore; Ferrero, Luisa; Cortese, Maria Grazia; Lonati, Luca; Teruzzi, Elisabetta; Basso, Eleonora; Morra, Isabella; Lemini, Riccardo; Sardi, Nicola; Gennari, Fabrizio (European Journal of Pediatric Surgery Reports, 2019)
Lipoblastomas are rare benign mesenchymal tumors that arise from embryonal fat cells.They are usually discovered in infants and children under 3 years of age, and mostly occur in the trunk (from 10 to 60%, depending on the study) and extremities (from 40 to 45%), while head and neck localizations are rare, with only five cases described to date.We report on three cases of lipoblastomas in infants younger than 4 years, with unusual localizations: one intra-abdominal, discovered during a laparotomy for an intussusception; one pelvic, misdiagnosed as an ovarian mass; and one gluteal with a pelvic extension.All children underwent magnetic resonance imaging as preoperative workup. All tumors were completely resected with free surgical margins and ultrasonographic follow-up was uneventful for all patients.
Keywords: lipoblastoma; surgery; children